A qualitative exploration of escalation of care in the acute ward setting. Issue 3 (12th December 2019) - Ede, Jody; Jeffs, Emma; Vollam, Sarah; Watkinson, Peter
Abstract: Background: "Failure to Rescue" includes failing to prevent avoidable patient deterioration and death. Despite its use, delays in care escalation still affect patient outcomes. Aims and Objective: The aim of this qualitative service evaluation was to map the barriers and facilitators to the escalation of care in the acute ward setting and identify those that are modifiable. Design: A total of 55 hours of qualitative observations were completed to capture care escalation events. These were conducted at two hospital sites in one National Health Service trust. Methods: Observations were iterative, with research team meetings being used to discuss the data and future methods. Field notes were analysed thematically by two researchers, extracting data on barriers and facilitators to escalation of care. Results: Clinical nursing staff challenged the sensitivity and specificity of Early Warning Scores, describing tool failings in certain clinical scenarios. Staff did not escalate based on the alerting Early Warning Scores alone but used other clinical factors, such as bleeding, which are not necessarily captured in the scoring systems. Staff frequently did not re‐escalate low‐level scores. Patient and non‐patient factors identified as posing barriers to escalation were complex care needs, patient outlier status, and involvement of multiple care teams. Factors negatively affecting the chain of communication during escalation were team tension, staffing levels, and inadequate handover. Conclusion: This service evaluation identified barriers and facilitators to the escalation of care in the acute ward setting. Unlike other studies, we found that re‐escalation or tracking of deterioration was problematic. Patients identified as being at a higher risk of escalation failure included complex patients, outliers, and patients with multiple care teams. Relevance to clinical practice: This service evaluation demonstrates continuing health care communication barriers. Patient groups (complex patients and outliers) risk process failures during escalation. This can be applied in clinical practice by staff anticipating problems in these patients, documenting clear escalation pathways.